Performing internal security framework: Guidelines for developing PhD frameworks - Kennedy Kaumba Mabuku (Khazanah Pendidikan Islam, 2023)
The study emerged from a doctoral thesis aimed at exploring internal security preservation in Namibia, a core mandate of the police force. It provides guidelines for crafting PhD frameworks in alignment with the internal security framework. The guidelines encompass various stages, including extensive literature review, contextualization to specific issues, component selection, assumption definition, framework naming, and acknowledgment of limitations. The paper underscores the importance of a thorough literature review to establish a foundational understanding, enabling critical analysis and substantiating framework development. Practical application and relevance to the research problem are emphasized. Mind mapping is employed to ensure coherence and differentiation from existing models. Naming the framework is deemed crucial, reflecting its primary concept. Acknowledging limitations fosters nuanced understanding and academic transparency. The "Framework for Performing Internal Security" integrates stakeholder collaboration, shared responsibility, and civil stakeholder training, addressing multifaceted challenges in internal security and offering insights for policing and security research.